Measuring Faculty Excellence: Introducing a Model - Anoush Dehnadi Moghadam (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Dear Editor Academic development has been a major topic of discussion in higher education in the United States since the 1960s (1). According to a comprehensive study of 190 higher education institutions from 1965 to 1985, faculty evaluation of faculty was considered one of the most common vitality strategies (2). The most frequent finding of this study was that faculty vitality programs followed by effective connection and continuity of faculty development with the mission and policies of the institution as a key issue. The role of faculty competence and the quality of teaching in training effective graduates is well-known. The European Union high level group on modernization of higher education  has identified the Assessment of teaching competence as a foundation for appointment and progression (3). Assessing the performance and excellence of faculty members, who are the core of university human resources, is a challenging issue. There are various criteria for this evaluation, which generally focus more on research performance, while the main objective of hiring faculty members has been the development of education. The common structure of academic scoring,  rewarding  research  More than teaching (4). The question now arises: "Can faculty members' research be related to student learning and improving the quality of education?" For example, would the teaching effectiveness of a faculty member with 20 articles be twice as effective as that of another with 10 articles? Different variables affect this issue, for example learner surveys (older studies) (5), learning outcomes (newer studies) (6), the type and number of universities studied (research-oriented or teaching-oriented), the presence of top researchers, other capabilities of the faculty member, and the existence of standardized data for learning outcomes at different levels of higher education. In summary, if education in research-based universities lacks the necessary status and credibility, the relationship between research output and education quality will not be positive. Moreover, the cultural climate of the university affects the excellence of education. Medical education has undergone significant changes in recent years owing to advances in medical knowledge, changes in healthcare delivery systems, patients' needs and expectations, and the emergence of new learning technologies, which have consequently transformed the role of medical educators (7). Therefore, a scientific approach is needed to evaluate educational performance, as outlined by Harden (8). Education, or the art of teaching, is a complex combination of knowledge and art that must be purposefully defined in terms of its acquisition and criteria for excellence (9). According to the model presented by Harden, educational excellence is equal to the product of three components: 1) technical skills, 2) approach to teaching , and 3) professional competence. Excellence Score = Technical Skills × approach to teaching × Professional Competence The multiplication method was chosen because the presence of competence in all three areas is mandatory, meaning that the absence of competence in one area makes the result equale to  zero. Technical skills include information provider, role model facilitator, evaluating, curriculum planning , educational resource developer; approach to teaching  includes following scientific principles, professional attitude and ethics, decision-making, and teamwork; professional competence (personal development) consists of skill development and scientific promotion, professionalism, self-audit, portfolio, commitment, and research (Figure 1).